High concentrations of aluminum in maternal serum and placental tissue are associated with increased risk for fetal neural tube defects. (December 2021) - Liu, Mengyuan; Wang, Di; Wang, Chengrong; Yin, Shengju; Pi, Xin; Li, Zhiwen; Wang, Linlin; Liu, Jufen; Yin, Chenghong; Jin, Lei; Ren, Aiguo
Abstract: Aluminum (Al) 1 is ubiquitously present in the environment, and human exposure to Al is common. Al has been reported to be involved in various human diseases and adverse pregnancy outcomes, including neural tube defects (NTDs). This study aimed to examine the association between prenatal Al exposure and the risk for NTDs using Al concentrations in maternal serum and placental tissue. The subjects were recruited from six counties/cities in the Shanxi province of northern China from 2003 to 2016. Al concentrations in both types of specimens were assessed using inductively coupled plasma-mass spectrometry. In the maternal serum cohort (200 cases and 400 controls), compared to the lowest tertile concentration of Al, the highest Al tertile was associated with 2.42-fold (95% confidence interval, 1.23–4.87) increased risk after adjustment for confounding factors. In the placental tissue cohort (408 cases and 593 controls), the highest tertile of Al also tended to be associated with an elevated risk for NTDs [adjusted odds ratio, 1.60 (0.94–2.70)]. When analyzed by NTD subtypes, the highest Al tertile was associated with an increased risk for anencephaly in both cohorts after adjustment for confounders [odds ratio, 1.97 (1.15–3.48) in the maternal serum cohort; odds ratio, 4.75 (2.01–12.00) in the placental tissue cohort]. Taken together, using concentrations of Al in maternal serum and placental tissue as exposure markers, we found that prenatal exposure to higher levels of Al is a risk factor for fetal NTDs, especially for the anencephaly subtype. Graphical abstract: Image 1 Highlights: Al concentrations in maternal serum and placenta were used as exposure markers. Exposure levels between neural tube defect (NTD) cases and controls were compared. A higher level of Al in both specimens was associated with an elevated risk for NTDs. A higher level of Al was associated with an increased risk for anencephaly subtype.